The human side of project management: an investigation of critical chain concepts in the Argentinean Project Environment - Weydt, Ingunn Kristine (2008)
The global marketplace is rapidly intensifying. Longer product sales lives, greater profit margins or simply survival, is dependent on management¿s ability to create and lead change. Project Management has become an important competency, combined with other business practices to adapt to the trend of changing conditions. Critical Chain is a relatively new project methodology, elaborated by Eliyahu Goldratt in order to complete projects faster, make more efficient use of resources and securing the project deliverables. The methodology is based on the assumption that traditional project techniques such as CPM and PERT, do not recognize critical human behavior. The methodology claims that many project failures are a direct result of how safety is built into the task delivery times, and then wasted by human behavior such as Student Syndrome, Parkinson Law and Multitasking. However, there has been little or no previous research regarding this topic in the Argentine marketplace. This study intended to investigate to what extent the human behavior concepts of critical chain project management are present, by performing in-depth interviews with Argentine project stakeholders. It appears that the four human behavior concepts are present in Argentina and that the majority of Argentine companies are yet to apply project management techniques.